2019
DOI: 10.1039/c8cp07393g
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization reaction dynamics of an inverse type diarylethene derivative as revealed by time-resolved absorption and fluorescence spectroscopies

Abstract: Time-resolved absorption and fluorescence spectroscopies revealed the cyclization reaction dynamics of an inverse diarylethene derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Many experiments, often complemented by TDDFT calculations, were conducted using a femtosecond transient absorption spectroscopy technique to study the mechanism of the ring-closure and photoreversion reactions of dithienylethene molecules dissolved in solvents. [2][3][4][5] A concern exists indeed about the ring-closure reaction, as the open-ring isomer has several conformers which are in thermal equilibrium at room temperature. They fall into two categories depending on whether the aromatic groups of the side chains are parallel (P) or antiparallel (AP) to each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experiments, often complemented by TDDFT calculations, were conducted using a femtosecond transient absorption spectroscopy technique to study the mechanism of the ring-closure and photoreversion reactions of dithienylethene molecules dissolved in solvents. [2][3][4][5] A concern exists indeed about the ring-closure reaction, as the open-ring isomer has several conformers which are in thermal equilibrium at room temperature. They fall into two categories depending on whether the aromatic groups of the side chains are parallel (P) or antiparallel (AP) to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Only AP isomers can undergo the ring closure reaction. Recently, Sotome et al 3 showed that 1,2-bis(3-methyl-5-phenyl-2-thienyl)perfluorocyclopentene (an “ inverse ” dithienylethene molecule) has one P and two AP conformers, but only one of the former makes the ring-closure reaction. Jarota et al , 2 Li et al 4 and Hamdi et al 5 investigated various “ normal ” dithienylethene molecules dissolved in solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53] On the other hand, the 2thienyl substituted "inverse type" diarylethenes undergo ringclosure reactions under irradiation in the short wavelength region, and some of them are known to be fluorescent in their open forms (OFs). 54 While these chemical modifications are key to customize the photophysical properties, the studies of sulfone (SO 2 ) and "inverse type" diarylethenes were focused on highly symmetric structures.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth understanding of relevant photophysical and photochemical processes of photoswitches is of fundamental importance for the design of novel photoswitches with better performances. Therefore, many time-resolved spectroscopical works have been carried out to explore the underlying photochromic mechanism of various diarylethenes [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Particularly, Jäschke’s group applied femtosecond transient absorption spectroscopy to study the photoinduced pericyclic and cycloreversion reactions of PS-IV [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%